Salivary Chromogranin A: Useful and Quantitative Biochemical Marker of Affective State in Patients with Amyotrophic Lateral Sclerosis - Obayashi, Konen; Sato, Kimiko; Shimazaki, Rie; Ishikawa, Tomoko; Goto, Katsumasa; Ueyama, Hidetsugu; Mori, Teruaki; Ando, Yukio; Kumamoto, Toshihide (Internal Medicine, 2008)
Objective To evaluate the affective state biochemically and quantitatively in amyotrophic lateral sclerosis (ALS) patients using salivary chromogranin A (CgA) measurement. Subjects and Methods Twelve moderate and 12 terminal ALS patients defined using the ALS Health State Scale were studied. The correlation between salivary CgA levels and the 40-item ALS assessment questionnaire (ALSAQ-40) scores was investigated in 12 moderate ALS patients. Moreover, salivary CgA levels in 12 terminal ALS patients, in whom the emotional functioning score could not be assessed, were compared with those in 12 moderate ALS patients, 7 patients with tube-fed vascular dementia, and in 26 healthy volunteers. Results There were individual differences in salivary CgA levels in spite of similar severity of disease; however, mean salivary CgA levels in terminal ALS patients, in whom the emotional functioning score based on interview could not be assessed, was significantly higher (12.58±2.79 pmol/mL) than in patients with moderate ALS (6.36±1.62 pmol/mL, p<0.05), tube-fed vascular dementia (4.04±2.04 pmol/mL, p<0.01), and healthy volunteers (3.77±1.90 pmol/mL, p<0.01). Moreover, a statistically significant positive correlation was observed between salivary CgA levels and emotional functioning scores on ALSAQ-40 in moderate patients (r=0.892, p<0.01). Conclusion Salivary CgA may be a useful and quantitative biochemical marker of the affective state, not only in moderate, but also in terminal ALS. Periodic salivary CgA measurements over the long term and/or in various situations could have therapeutic implications for the quality of life of these patients.